Implementasi Evaluasi Pembelajaran Berbasis Digital di Sekolah Dasar: Studi Multi-Situs: STUDI MULTI-SITUS - Diana Dwi Putri; Jeni Pristiawati; Rafifa Fadhlurahmi; Siti Fatihatun Najwa; Alifah Fawwazah; Muhammadi Muhammadi; Ranti Meizatri (STIKes Ibnu Sina Ajibarang, 2025)
This research aims to identify the implementation of digital-based learning evaluation in elementary schools, analyze the types of digital media used, and evaluate its advantages and disadvantages. Observational studies were conducted in seven different elementary schools with diverse characteristics, including public and private, national and international schools. The research method uses a descriptive qualitative approach with passive participatory observation techniques, semi-structured interviews, and documentation. The results show that elementary schools have adopted various digital evaluation platforms such as Google Form, Quizizz, Wordwall, and Learning Management System with varying levels of implementation. The findings revealed that digital evaluation media increases student motivation and participation, speeds up the assessment process, and provides direct feedback. However, there are obstacles in the form of limited technological infrastructure, a gap in the digital literacy of teachers and students, and dependence on the internet network. This research provides recommendations for infrastructure improvement, continuous training for teachers, and the development of a holistic evaluation system that accommodates cognitive, affective, and psychomotor aspects.